Numerical Simulation of Finite-Rate Catalytic Model Based on ReaxFF-MD - Jiahao SONG; Fan MO; Zhenxun GAO (气体物理)
At present, when CFD method is used to predict surface heat flux, it is generally assumed that the wall condition is full-catalytic wall or non-catalytic wall. Heat flux prediction can be greatly affected by different wall catalytic conditions, and a more reasonable numerical solution can be obtained by using finite-rate catalytic model. However, due to the nonlinear, nonequilibrium, and multiscale characteristics of the catalytic recombination process of high-enthalpy chemical reaction flows on material surfaces, it is extremely difficult to accurately describe the finite-rate catalytic model. In this paper, a finite-rate catalytic model describing the interaction of O and N atoms with SiO2 surface was constructed by ReaxFF-molecular dynamics method based on the theory and simulation at the microscale. The reentry flow fields of space shuttle orbiter under different catalytic conditions were calculated and compared. The results show that the predicted heat flux of the finite-rate catalytic model agrees well with the flight test data of STS-3 in the altitude range of 70.1 km to 57.8 km, and the model has a certain degree of accuracy.